Acrinathrin: (S)-cyano(3-phenoxyphenyl)methyl (Z)-(1R,3S)-2,2-dimethyl-3-{2-[2,2,2-trifluoro-1-(trifluoromethyl)ethoxycarbonyl]vinyl}cyclopropane-1-carboxylate - Hojin Yang; Tae Ho Kim; Ki-Min Park; Jineun Kim (Acta Crystallographica Section E, 2011)
In the title compound, C26H21F6NO5, the dihedral angle between the cyclopropane ring plane and the vinyl group plane is 79.3 (3)°. The dihedral angle between the benzene and phenyl ring planes in the phenoxybenzyl group is 82.7 (1)°. In the crystal structure, weak intermolecular C—H...π interactions and C—H...F hydrogen bonds contribute to the stabilization of the packing.